The new perspective on understanding the mechanisms of cardiovascular diseases development - Ulyana Khovantseva; Diana Kiseleva; Vadim Cherednichenko; Deyyara Chakal; Denis Breshenkov; Yuliya Markina; Rustam Ziganshin; Eduard Charchyan; Alexander Markin (Scientific Reports)
Abstract Cardiovascular diseases (CVD) are one of the leading causes of death worldwide. From a modern point of view, endothelial dysfunction is considered as a key factor leading to the development of CVD. However, scientists have suggested that the main causes of the development of CVD might be functional disorders and phenotypic modulation of smooth muscle cells (SMCs) that make up the vascular wall. In this regard, the aim of our study was to evaluate the functional features of SMCs isolated from the tunica intima and from the tunica media of the thoracic part of the human aorta in patients with CVD. In our research we showed that phenotypic switching can occur in SMCs isolated from patients with aneurysms (n = 6), resulting in remodeling of the extracellular matrix and impaired interaction between cellular receptors. In addition, it is probable that the activation of complement-mediated phagocytosis as a result of LDL internalization by SMCs might be one of the key mechanisms in the process of aneurysm development.